Implementasi Algoritma Zhu-Takaoka Pada Data Repository Linux Berbasis Web - Khairul Abdi Dongoran; Nelly Astuti Hasibuan; Sumiaty Hutabarat; Garuda Ginting; Saidi Ramadan Siregar (JURIKOM (Jurnal Riset Komputer), 2021)
When you use a software keyword that is searched on a website, there are a lot of sites that provide the software, it takes a long time to get the files needed because they are looking for files manually and there are no categories or groupings of software needed. In correcting the writer using the Zhu-Takaoka Algorithm, Zhu-Takaoka is a modified algorithm of the Boyer-Moore algorithm. The Zhu-Takaoka algorithm uses a two-dimensional array to calculate and execute functions from left to left which allows you to make mistakes, find applications that can be done quickly and easily with the stack of programs or applications in the repository. The expected design of this Linux repository application can run well in all devices that have a browser, and this designed application also allows you to search for debian (.deb) Linux programs using the name of the software you are looking for.